Formulación de una propuesta de mejora para el proceso de selección de proveedores de la empresa Previcar S.A.S, basados en el numeral 8.4 de la norma ISO 9001: 2015 y numeral 4.4.6 Literal B de la norma 18001: 2007 (2017)
In the midst of an increasingly competitive market for organizations, there is a need to improve each of the processes within it that become the optimization and efficiency of its resources, thus a single management of the quality and safety at work, will allow to detect opportunities for the risk of damages risks generated by clients and / or any other type of persons who intervene directly or indirectly with themselves; This creates the opportunity to comply with the requirements stipulated by the regulations and in turn, the companies wish to implement the rules created for this purpose. Based on the above, the general of the companies must implement the Integrated Management Systems, which will allow, through their own findings, to generate value chains in the interior that are finally reflected in added value for their final customers.